The malate shuttle detoxifies ammonia in exhausted T cells by producing 2-ketoglutarate - Weisshaar, Nina; Ma, Sicong; Ming, Yanan; Madi, Alaa; Mieg, Alessa; Hering, Marvin; Zettl, Ferdinand; Mohr, Kerstin; Ten Bosch, Nora; Stichling, Diana; Büttner, Michael; Poschet, Gernot; et al. (Nature immunology, 2023)
Abstract - The malate shuttle is traditionally understood to maintain NAD - + - /NADH balance between the cytosol and mitochondria. Whether the malate shuttle has additional functions is unclear. Here we show that chronic viral infections induce CD8 - + - T cell expression of GOT1, a central enzyme in the malate shuttle. - Got1 - deficiency decreased the NAD - + - /NADH ratio and limited antiviral CD8 - + - T cell responses to chronic infection; however, increasing the NAD - + - /NADH ratio did not restore T cell responses. - Got1 - deficiency reduced the production of the ammonia scavenger 2-ketoglutarate (2-KG) from glutaminolysis and led to a toxic accumulation of ammonia in CD8 - + - T cells. Supplementation with 2-KG assimilated and detoxified ammonia in - Got1 - -deficient T cells and restored antiviral responses. These data indicate that the major function of the malate shuttle in CD8 - + - T cells is not to maintain the NAD - + - /NADH balance but rather to detoxify ammonia and enable sustainable ammonia-neutral glutamine catabolism in CD8 - + - T cells during chronic infection.